2017
DOI: 10.1075/itl.168.1.03jaf
|View full text |Cite
|
Sign up to set email alerts
|

Advanced and intermediate EFL learners’ perceptions and practices of autonomous learning

Abstract: This study examined Persian intermediate and advanced EFL learners’ perceptions regarding (a) their own and their teachers’ responsibility in learning language autonomously; (b) their decision making ability in learning language autonomously; and (c) their autonomous learning activities inside and outside the classroom. To this end, a questionnaire designed by Chan, Spratt, and Humphrey (2002) was distributed among 67 intermediate and 65 advanced EFL learners. Statistical analysis of students’ answers showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The benefits of autonomous learning are innumerable and beyond dispute. Thus, investigating students' perception of autonomous learning is necessary (Jafari et al 2017). This study reveals that students engage in autonomous learning activities with an overall mean of 3.2 indicating that students have little exposure and experience in autonomous learning at their current institution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefits of autonomous learning are innumerable and beyond dispute. Thus, investigating students' perception of autonomous learning is necessary (Jafari et al 2017). This study reveals that students engage in autonomous learning activities with an overall mean of 3.2 indicating that students have little exposure and experience in autonomous learning at their current institution.…”
Section: Discussionmentioning
confidence: 99%
“…Such skills are being encouraged and considered as main goals of education (Sedighi & Tamjid 2016;Üstünlüoğlu 2009). For these reasons, investigating students' perception about autonomous learning is necessary (Jafari, Ketabi, & Tavakoli 2017). Determining students' readiness towards autonomous language learning will provide invaluable information on how to promote and nurture autonomy in various educational levels.…”
Section: Introductionmentioning
confidence: 99%
“…Along with the technology advancement, autonomy in language teaching and learning sees technology as the major aspect of its application. It is proven by the research result of autonomous language learning implementation which indicates that learners are highly dependent on the technology and they were also aware that technology assists them to achieve their learning goals by providing various types of sources (Inayati, 2014(Inayati, , 2016. In line with this, Bravo et al (2017) agree that the enhancement of autonomous language learning goes hand in hand with technology advancement.…”
Section: Technology For Autonomous Language Learningmentioning
confidence: 95%
“…Students who were less successful in school often worked in groups, did not voice their ideas or ask questions, and relied on the instructor rather than on themselves to evaluate how much they had learned rather than reflecting on their own progress. Futhermore, Jafari et al(2017) examined Persian intermediate and advanced EFL learners' autonomus perceptions and revealed that learners' perceptions were affected by their previous educational experiences. Previous studies have shown that students with high levels of English proficiency are more independent, self-motivated, and self-assured in their capabilities to learn the language (Schmenk,2006).…”
Section: Literature Reviewmentioning
confidence: 99%